Analysis of Warm and Cold Season Thunderstorms for Istanbul - Muhammed Başpınar; Veli Yavuz (Doğal Afetler ve Çevre Dergisi)
A thunderstorm (TS) is a severe weather phenomenon characterized by intense showers, hail, lightning, thunder, tornadoes, turbulence, and gusty winds. It occurs in vertically developed Cumulonimbus (Cb) clouds due to atmospheric instability and has a spatial resolution (meso-scale) of 1 - 100 km. This phenomenon occurs mainly in spring and early summer in our country due to the uplift and condensation of moist and unstable air masses. However, in recent years, these events have become more frequent during mid-summer, early autumn, and even winter months. In this study, the characteristics of TS events in Istanbul, covering the period from 2013 to 2022, including the warm season (May-September) and the cold season (October-April), were examined, and the atmospheric conditions under which they occur were identified. Aviation observations from Sabiha Gökçen International Airport were used to determine the occurrence of TS events, and data from Istanbul Kartal Radiosonde Station were analyzed to obtain upper-level atmospheric parameters. The occurrence of individual TS events or their association with other phenomena was investigated, and the statistics were presented. The daily, monthly, and yearly analyses of TS events during the period were conducted, and the changes in meteorological parameters for both the warm and cold seasons were statistically presented. Meteorological parameters such as temperature, dew point temperature, wind speed, wind direction, and relative humidity were analyzed for both warm and cold season TS events. Additionally, the average changes in each thermodynamic index and atmospheric stability parameter for hot and cold season oraj events were examined using a total of eight indices and parameters.